2022
DOI: 10.1111/jfbc.14191
|View full text |Cite
|
Sign up to set email alerts
|

Ferula assa‐foetida oleo gum resin ethanolic extract alleviated the pancreatic changes and antioxidant status in streptozotocin‐induced diabetic rats: A biochemical, histopathological, and ultrastructural study

Abstract: The current research examines the effects of administration of 150 and 250 mg/kg body weight/day of ethanolic Ferula assa‐foetida L. oleo gum resin extract (FAE) for 42 days in streptozotocin‐induced diabetes in rats. On day 42, all rats were euthanized; HOMA‐β, HOMA‐IR, and QUICKI levels in pancreas were examined histopathologically and ultrastructurally . Low‐dose FAE (150 mg/kg) treatment resulted in significant improvement in serum glucose, insulin and superoxide dismutase, glutathione, and catalase levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Cobra Venom Factor (CVF) is an acidic glycoprotein that can reduce complement C3 and thus inhibit immune responses and inflammation [ 49 , 50 ]. Therefore, it may be hypothesized that the effects of the venom are mediated by protecting pancreatic β-cells from the damaging effects of oxidative stress, allowing for the preservation of regenerated β-cells in the islets, as suggested for other agents with antioxidant activity [ 32 , 33 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cobra Venom Factor (CVF) is an acidic glycoprotein that can reduce complement C3 and thus inhibit immune responses and inflammation [ 49 , 50 ]. Therefore, it may be hypothesized that the effects of the venom are mediated by protecting pancreatic β-cells from the damaging effects of oxidative stress, allowing for the preservation of regenerated β-cells in the islets, as suggested for other agents with antioxidant activity [ 32 , 33 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-performance liquid chromatography revealed the presence of quercetin (flavonoid) in S. torvum fruit extract. It has been shown that quercetin possesses antidiabetic activity in streptozotocin-induced diabetic rats through regeneration of pancreatic islets which increases insulin secretion ( 27 ). This histological evidence may also account for the hypoglycemic activity of the S. torvum fruit extract.…”
Section: Discussionmentioning
confidence: 99%